PEMBERDAYAAN IBU RUMAH TANGGA DI PANORAMA MELALUI EDUKASI BUDIDAYA SAYURAN DENGAN HIDROPONIK DAN MEDIA TANAM - Resti Fajarfika; Tanti Dewinggih (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Vegetables have many benefits for the body so they become an important menu in meeting the nutritional needs of the family. Vegetables can be grown on land, polybags, and hydroponically. In housing or urban areas that have limited land, you can plant in your yard by selecting the appropriate planting method. The purpose of this service is to empower housewives in urban areas through education on vegetable cultivation. Methods of activities carried out are surveys, counselling, discussions, and direct practice. The results of the activities that have been carried out are that housewives can directly practice hydroponic vegetable planting and planting media. In addition, it adds insight into vegetable seeds that can be planted